Building real-time analytics applications - Briskman, Darin (O'Reilly Media, Inc., 2023)
Every organization needs insight to succeed and excel, and the primary foundation for insights today is data—whether it's internal data from operational systems or external data from partners, vendors, and public sources. But how can you use this data to create and maintain analytics applications capable of gaining real insights in real time? In this report, Darin Briskman explains that leading organizations like Netflix, Walmart, and Confluent have found that while traditional analytics still have value, it's not enough. These companies and many others are now building real-time analytics that deliver insights continually, on demand, and at scale—complete with interactive drill-down data conversations, subsecond performance at scale, and always-on reliability.